Synthesis of Zeolite-X Supported On Glasswool for CO2 Capture Material: Variation of Immersion Time and NaOH Concentration at Glasswool Activation - Anggita R.K. Wardani; Nurul Widiastuti (Universitas Gadjah Mada, 2016)
Zeolite X supported on fiber material (glasswool) was successfully synthesized using a simple hydrothermal method. Variation of immersion time and NaOH concentration were used for glasswool activation. Activation process of glasswool has effects toward crystallinity and growth of zeolite X on glasswool surface. The results of characterization using XRD, SEM and AFM showed that zeolite X crystal grew on glasswool surface with high crystallinity using NaOH concentration 4M for 24 h. BET surface area and pore characteristics were analyzed by N2 isothermal adsorption. Carbon dioxide adsorption measurement using gravimetric method showed that zeolite X supported on glasswool has capability to capture carbon dioxide at room temperature up to 2.83 weight %.